Bibiliometrics Menggunakan Analisis R-Bibiloshiny Resistensi Insulin pada Obesitas Kelompok Dewasa Database Scopus (2019-2025) - Krish Naufal Anugrah Robby; Rachmad Gusti Irwansyah; Leersia Yusi Ratnawati; Candra Bumi; Irma Prasetyowati; Isa Ma’rufi; Dedek Sutinbuk; Farida Wahyu Ningtyias; Anita Dewi Prahastuti Sujoso; Dewi Rokhmah; Ida Srisurani Wiji Astuti (Universitas Muhammadiyah Manado, 2024)
contributing to the global burden of type 2 diabetes, cardiovascular diseases, and other metabolic complications. This bibliometric study aims to analyze trends, thematic focuses, and collaborations in scientific publications related to insulin resistance in adult obesity, utilizing data from the Scopus database covering the period from 2019 to 2025. Bibliometric tools such as RStudio, Biblioshiny, and VoS Viewer were employed to extract and visualize findings from 8,037 publications. The results reveal that research activity peaked in 2021, followed by a decline in subsequent years. Dominant keywords, such as